2020
DOI: 10.1002/tie.22132
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐national investigation of trait antecedents of mobile‐banking adoption

Abstract: Although there is a near agreement in the literature on the main predictors of consumers' attitudes toward technological innovation, the potential ways through which personal traits and national environmental differences contribute to significant variations in mobile‐banking adoption have received limited attention. Based on insights from innovation adoption and personality research, this study tested a model of mobile‐banking adoption using data from a developed and a developing country. Survey data came from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 72 publications
(184 reference statements)
1
14
0
Order By: Relevance
“…In the banking transaction context, the impact of Attitude Towards Mobile Banking (ATT), Subjective Norms (SN), and Perceived Behavioral Control (PBC) on potential customers' Behavior Intention (BI) to use technology-based self-service are empirically validated (Giovanis & Athanasopoulou, 2017;Khasawneh & Irshaidat, 2017). More specifically, researchers applied the theory of planned behavior and with additional variables to predict the behavioral intention of using mobile banking (Aboelmaged & Gebba, 2013;Ayudya, & Wibowo, 2018;Frimpong et al 2020;Luarn, & Lin, 2005). However, there is a dearth of research that comprises the additional variables in existing TPB during COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…In the banking transaction context, the impact of Attitude Towards Mobile Banking (ATT), Subjective Norms (SN), and Perceived Behavioral Control (PBC) on potential customers' Behavior Intention (BI) to use technology-based self-service are empirically validated (Giovanis & Athanasopoulou, 2017;Khasawneh & Irshaidat, 2017). More specifically, researchers applied the theory of planned behavior and with additional variables to predict the behavioral intention of using mobile banking (Aboelmaged & Gebba, 2013;Ayudya, & Wibowo, 2018;Frimpong et al 2020;Luarn, & Lin, 2005). However, there is a dearth of research that comprises the additional variables in existing TPB during COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental drivers were investigated as a single construct in attempt to provide a holistic view on how a person's surroundings can encourage or discourage him or her from using innovative Fintech services. Although literature is lacking in term of studying environment as a predictor, there are studies that gave attention to the influence of environment (Frimpong et al, 2020, Putri et al, 2020. Putri et al (2020), for example, investigated the impact of environmental factors on the continuing usage of mobile payment services, which are a sort of Fintech service.…”
Section: Discussionmentioning
confidence: 99%
“…Technological readiness is used to refer to consumer belief on the available resources and support to complete behavior, such as the availability of needed technical infrastructure and facilities as well as the availability of the support to make the process of using a service fast and easy (Venkatesh et al, 2012). Literature supported that people adoption of innovation was impacted by nation technological environment (Archibugi & Coco, 2004;Bhatt & Bhatt, 2016;Frimpong et al, 2020). Past studies demonstrated that technical conditions positively impact adoption of new technology (Gerlach & Lutz, 2019;Oliveira & Martins, 2010).…”
Section: Technological Readiness (Tr)mentioning
confidence: 99%
“…While most studies investigated mobile banking adoption in a single country (although the countries studied in the corresponding case are diverse), some studies (Changchit et al, 2020), (Frimpong et al, 2020)) compared it between developed and developing countries. For example, (Changchit et al, 2020) compared mobile banking perceptions among consumers in the U.S. (355 respondents) and in Thailand (400 respondents) using factor analysis and statistical ttests data analysis.…”
Section: Mobile Bankingmentioning
confidence: 99%
“…On average, the U.S. subjects' attitudes toward mobile banking are significantly higher than Thai subjects. (Frimpong et al, 2020) focused on a cross-national investigation of trait antecedents of mobile-banking adoption between the UK and Ghana. Based on insights from innovation adoption and personality research, this study tested a model of mobile-banking adoption using data from a developed and a developing country.…”
Section: Mobile Bankingmentioning
confidence: 99%